Study Komparasi Penambahan Palm Oil Ash Dengan Bantuan Semen Berdasarkan Nilai California Bearing Ratio: Comparative Study Of Addition Of Palm Oil Ash With Support Of Cement Based On California Bearing Ratio - Norseta Ajie Saputra; Noviyanthy Handayani; Benny Santoso (Media Ilmiah Teknik Sipil, 2023)
High water content, water saturation, and low carrying capacity are characteristics of clay soils. The road body may have an uneven surface. On the other hand, in the dry season it will harden and have a high  carrying capacity so that a lot of dust is scattered on the road and blocks the driver's view. As a result, the neighborhood can experience traffic jams and accidents. Check the CBR and PI values to see if there is an increase in clay after stabilization using a mixture of Palm Oil Fuel Ash and cement with variations (0%  POFA + 2% Cement), (3% POFA + 2% Cement), (5% POFA + 2% Cement), and (7% POFA + 2% Cement). Test method Sieve Analysis, Atterberg Limit, Specific Gravity, Moisture Content, Compaction and CBR. Cement and palm oil bunch ash produced a CBR value of 7.4% compared to a natural soil CBR value of 1.59%. The CBR value of the soil will increase, the dry unit weight value will decrease, and the plasticity  value will decrease with the higher proportion of Oil Palm Bunch Ash and cement